2001
DOI: 10.1186/1471-2296-2-3
|View full text |Cite
|
Sign up to set email alerts
|

S-carboxymethylcysteine in the treatment of glue ear: quantitative systematic review

Abstract: Objective: To establish the clinical relevance of S-carboxymethylcysteine in the treatment of glue ear in children using measures approximating those saving a child from operation for grommet insertion.Data sources: Cochrane Library, MEDLINE, EMBASE, PubMed, reference lists and reviews were used for randomised controlled trials comparing S-carboxymethylcysteine with placebo. Seven trials involving 283 children and 146 ears were found. Review methods:Studies were randomised, double-blind comparisons of Scarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Although the contribution of mucus production on asthmatic airways is still unclear, MUC5AC and other mucin genes have been shown to be related to asthma status in clinical studies [7] and in animal models [8]. S-carboxymethylcysteine (S-CMC) has been used as a mucoregulator for treating chronic obstructive pulmonary disease (COPD), asthma and chronic nasal diseases, such as chronic sinusitis or otitis media, with some efficacy [9][10][11]. However, there have been few studies addressing potential efficacy or mechanism of action in allergen-induced asthma.…”
mentioning
confidence: 99%
“…Although the contribution of mucus production on asthmatic airways is still unclear, MUC5AC and other mucin genes have been shown to be related to asthma status in clinical studies [7] and in animal models [8]. S-carboxymethylcysteine (S-CMC) has been used as a mucoregulator for treating chronic obstructive pulmonary disease (COPD), asthma and chronic nasal diseases, such as chronic sinusitis or otitis media, with some efficacy [9][10][11]. However, there have been few studies addressing potential efficacy or mechanism of action in allergen-induced asthma.…”
mentioning
confidence: 99%
“…Oral administration of S-CMC accelerated clearance of middle ear effusion in experimental otitis media with effusion [12]. Metaanalysis of seven articles showed that use of S-CMC resulted in a 35% improvement of otitis media with effusion compared with only 17% improvement in the control group [13]. In the present study, we investigated the effect of add-on administration of CAM to S-CMC for persistent inflammation after acute middle ear infection subsided.…”
Section: Discussionmentioning
confidence: 93%
“…[18] Moore et al evaluated 283 children in seven different studies and reported CMS as a safe drug for the treatment of OME. [19] In contrast to all of these studies, van der Merwe et al conducted a study on 60 people and compared bromhexin with placebo in delaying resolution of middle ear effusion. [20] In another study, CMS has been shown to have no effect on the viscosity of the treatment process and, it has been suggested that CMS is ineffective in the treatment of OME.…”
Section: Discussionmentioning
confidence: 99%